(untitled) (Medical Forum Monthly, 2026)
Objective: To compare periilioinguinal nerve block with subcutaneous wound infiltration in below umbilical surgeries in pediatric surgical patients. Study Design: Randomised control trial study Place and Duration of Study: This study was conducted at the department of Anaesthesiology, ICU and Pain medicine at Mohiuddin Islamic Medical College teaching hospital, Mirpur, AJK from 12th May till November, 2025. Methods: This study included fifty ASA I and II elective surgical pediatric patients in a teaching tertiary care hospital. Patients were randomized into group P (Periilioinguinal block) and group S (Subcutaneous infiltration). Endotracheal tube was inserted after general anesthesia induction with ketamine and propofol. Results: Fifty elective surgery patients were randomly assigned in two groups, group P (Periilioinguinal) and group S (Subcutaneous infiltration). The minimum age in group P and S was 10 months and maximum in group P is 9 years and group S is 8 years. There were 24 males in group P and 21 males in group S while 1 females in group P and 4 females in group S. Using FLACC score, no pain noted in thirteen patients in P group vs 5 in S group which was statistically significant at 1st hour postoperatively (p<0.005). Using NRS score, no pain noted in 13 patients in P group while 5 in S group which was statistically significant at 1st hour postoperatively (p<0.005). At 6th and 12 hours, more pain noted in S than P group but not statistically significant. (p 0.345). Conclusion: Periilioinguinal nerve block improves the pain management of pediatric surgical patients compared to subcutaneous wound infiltration with bupivavaine technique making it a valuable choice in multimodal analgesia in low income countries for elective and emergency surgeries pediatric anaesthesia.